FISCAL POLICY OTONOMI DAERAH (Kajian Penerimaan Fiscal Decentralization Di Provinsi Riau) - Muhammad Aras (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2019)
The implementation of regional autonomy in Indonesia is manifested in the form of delegation or handover of central government authority to regional governments, approved in Law Number 22 of 1999 which has been amended by UU Number 32 of 2003, concerning regional government. In the request for fiscal decentralization, it has been enacted since January 1, 2001, applied pursuant to UU Number 25 of 1999, concerning financial balance between the central government and regional governments. However, the aforementioned Law (UU No. 25/1999 and UU No.22 / 1999) does not regulate the distribution of duties on the provision of public goods (public services), for example, in the education and health sector, so that it can be announced about the spending authority allocated to the regions by the central government is delegated authority. Because it applies the principle of "money follows delegation of duties" (the function of money follows) or simply called the use of the budget according to its function, it does not run launched using run in decentralization. The Central Government must pay for expenditure that is the responsibility of the local government. Kerana is the central government responsible for fiscal decentralization in the form of a financial balance between the central government and regional governments. Requesting regional governments that receive fiscal decentralization that has the obligation to produce public goods and public regulations according to the needs of the people in the region As a unitary state (unitary state), Indonesia consists of provinces (states) and regencies / cities (regencies / cities). Then the Riau Province is one of the provinces in Indonesia, which received the financial balance transfer funds. Budget decentralization consists of three categories, namely balance funds, special autonomy funds, and paid funds. All regions receive balance funds through a decentralized proportional policy according to the needs of each region including Riau Province.